Behaviour of precast beam-to-column connections by using partly hidden corbel / Rohani Mokhtar - Rohani, Mokhtar (2017)
The performance of precast concrete structures is greatly influenced by the behaviour of beam-to-column connections. A single connection may be required to transfer several loads simultaneously so each one of those loads must be considered in the design. A good connection combines practicality and economy which requires an understanding of several factors; strength, serviceability, erection and economics. This research focuses on the performance aspect of a specific type of beam-to-column connection using partly hidden corbel in precast concrete structures. The study presents the experimental assessment of the beam-to-column connection in precast concrete frames. The main objective of this study is to investigate the behaviour and capacity (such as the moment resistance) and the failure mechanisms within connection zone of a proposed connection by conducting experimental tests. Full-scale testing is conducted on three precast concrete exterior beam-to-column connections to determine their suitability as semi-rigid and partial-strength connections. The behaviour of a specific type of beam-to-column connection is examined; the connection uses a partly hidden corbel with different anchorage arrangements in precast concrete structures. The capacity (e.g., moment resistance) and failure mechanism of the connection are investigated, and experimental assessment of the proposed beam-to-column connection is performed under static and reversible loads. The classification and behaviour of the connection are defined by using moment–rotation (M–ϕ) data together with the characteristic response of the beam, which is known as the “beam line,” and the fixity factor under certain loadings in a flexurally cracked state. Based on experimental results, beam-line reveals beam-end’s moment of resistance, ME, rotational stiffness, and fixity factor. Besides that, the proposed precast beam-to-column connection BHC2-T2 and BHC3-T2 can be classified as semi-rigid and it falls under zone III (semi-rigid with medium strength), meanwhile, BHC1-T1 connection falls under zone II (semi-rigid with low strength). This demonstrates its ability to be applied for semi-rigid analysis of precast frames.